A Comprehensive Game Theoretical Defense Strategy in Demand Side Management Against Price Tampering Attacks - Fu, Rong; Chen, Jie; Zhang, Xiaofei; Zhang, Jie (Frontiers in Energy Research, 2021)
Price tamping attacks may cause market turbulence, attack detection and defense strategy are needed to study. Firstly, demand response characteristics are analyzed in a User Energy System. A quantitative model is established to describe the load changes caused by price tampering attacks. Secondly, a space-based cumulative intrusion detection method is proposed to pick up the discrepancy under tampering attacks. To verify the practicability of the proposed method, intrusion detection experiments are tested in the Principal Information and Safety Laboratory. Then, comprehensively considering the purchase of electricity from the power grid, self-generation, and load shedding, a quantitative model of attack consequences is established based on the allocation coefficient. Thus, the intrusion detection algorithm is used as a defense resource, and a demand-side defense protection strategy is formed to find an optimal deployment method based on non-cooperative game theory. The defensive protection strategy takes the quantitative model of attack consequences as the solution target, and solves the Nash equilibrium solution under different attack modes. Finally, in the IEEE-33 node system simulations, the defense resource is deployed using intrusion detection strategy, and the defense decision is executed to show the effectiveness of the comprehensive protection strategies.